Two pathogen reduction technologies—methylene blue plus light and shortwave ultraviolet light—effectively inactivate hepatitis C virus in blood products. Issue 5 (21st August 2012) - Steinmann, Eike; Gravemann, Ute; Friesland, Martina; Doerrbecker, Juliane; Müller, Thomas H.; Pietschmann, Thomas; Seltsam, Axel
<x xml:space="preserve">Abstract</x> BACKGROUND: Contamination of blood products with hepatitis C virus (HCV) can cause infections resulting in acute and chronic liver diseases. Pathogen reduction methods such as photodynamic treatment with methylene blue (MB) plus visible light as well as irradiation with shortwave ultraviolet (UVC) light were developed to inactivate viruses and other pathogens in plasma and platelet concentrates (PCs), respectively. So far, their inactivation capacities for HCV have only been tested in inactivation studies using model viruses for HCV. Recently, a HCV infection system for the propagation of infectious HCV in cell culture was developed. STUDY DESIGN AND METHODS: Inactivation studies were performed with cell culture–derived HCV and bovine viral diarrhea virus (BVDV), a model for HCV. Plasma units or PCs were spiked with high titers of cell culture–grown viruses. After treatment of the blood units with MB plus light (Theraflex MB‐Plasma system, MacoPharma) or UVC (Theraflex UV‐Platelets system, MacoPharma), residual viral infectivity was assessed using sensitive cell culture systems. RESULTS: HCV was sensitive to inactivation by both pathogen reduction procedures. HCV in plasma was efficiently inactivated by MB plus light below the detection limit already by 1/12 of the full light dose. HCV in PCs was inactivated by UVC irradiation with a reduction factor of more than 5 log. BVDV was less sensitive to the two pathogen reduction methods. CONCLUSIONS: Functional assays with human HCV offer an efficient tool to directly assess the inactivation capacity of pathogen reduction procedures. Pathogen reduction technologies such as MB plus light treatment and UVC irradiation have the potential to significantly reduce transfusion‐transmitted HCV infections.